BS EN 62133-2 AMD1. Secondary cells and batteries containing alkaline or other non-acid electrolytes. Safety requirements for portable sealed secondary lithium cells, and for batteries made from them, for use in portable applications. Part 2. Lithium systems (24th January 2020) - British Standards Institution,
No abstract available